Eating disorders and non-suicidal self-injury: Cluster analysis considering eating pathology, emotion dysregulation, and negative urgency - Gonçalves, Sónia (2022)
Research on the interplay between eating pathology, emotion dysregulation and negative urgency is needed to inform intervention approaches for patients with eating disorders and non-suicidal self-injury. This study aimed to investigate the characterization of patients with eating disorders and non-suicidal self-injury considering eating pathology, emotion dysregulation and negative urgency. This cross-sectional study evaluated 73 outpatients with eating disorders and non-suicidal self-injury (14-55 years; 68 women). A cluster analysis was performed using eating pathology, emotion dysregulation and negative urgency. Differences between clusters were explored on sociodemographic/psychological variables, eating disorder diagnostics and past/current non-suicidal self-injuryengagement. Three clusters were identified. Cluster 1 (n=29) (moderate severity) was characterized by high levels of eating pathology, but moderate emotion dysregulation and negative urgency. Cluster 2 (n=29) (high severity) was characterized by the highest scores in eating pathology, emotion dysregulation and negative urgency, and included more patients with current non-suicidal self-injury. Cluster 3 (n=15) (low severity) was characterized by the lowest levels of eating pathology, emotion dysregulation and negative urgency, and included more patients with past non-suicidal self-injury. These profiles highlight the importance of emotion dysregulation and negative urgency as treatment targets for eating disorders patients with current non-suicidal self-injury.